Cognitive-behavior therapy for sleep disorders at midlife. Issue 7 (July 2021) - Nowakowski, Sara; Meers, Jessica M.
Abstract : Abstract: Insomnia is a clinical disorder characterized as difficulty falling asleep, staying asleep, or waking too early. To meet diagnostic criteria for an insomnia disorder, these difficulties must be present for a minimum of 3 months and cause significant daytime impairment. Insomnia is common in women transitioning through menopause and frequently continues in the years after menopause. Cognitive-behavior therapy for insomnia (CBT-I) is a brief behavior treatment, with decades of evidence supporting its effectiveness across the adult lifespan, including midlife. This Practice Pearl highlights the rationale for CBT-I and describes treatment components, with specific considerations for its use in midlife women.